Modeling of Hydraulic Power Cylinder Seal Assembly Operation; Taishan Academic Forum - Project on Mine Disaster Prevention and Control "Chinese coal in XXI century: mining, green and safety", October 17–20 2014, Qingdao, China - Buyalich G. D. Gennadiy Daniilovich (2015, 2015)
The nature of the hydraulic power cylinder seal assembly operation with high working fluid pressure, different geometrical parameters of liptype seal, is revealed. The method of hermetic sealing process modeling according to the simplified model using finite element method is considered.